Determination of the triple oxygen isotopic composition of tropospheric ozone in terminal positions using a multistep nitrite‐coated filter‐pack system. (9th June 2021) - Xu, Hao; Tsunogai, Urumu; Nakagawa, Fumiko; Li, Yijun; Ito, Masanori; Sato, Keiichi; Tanimoto, Hiroshi
Abstract : Rationale: The triple oxygen isotopic composition (Δ 17 O) of tropospheric ozone (O3 ) is a useful tracer for identifying the source and is essential for clarifying the atmospheric chemistry of oxidants. However, the single nitrite‐coated filter method is inaccurate owing to the nitrate blank produced through the reaction of nitrite and oxygen compounds other than O3 . Methods: A multistep nitrite‐coated filter‐pack system is newly adopted to transfer the O‐atoms in terminal positions of O3 to nitrite on each filter to determine the Δ 17 O of O3 in terminal positions (denoted as Δ 17 O(O3 )term ). The NO3 − produced by this reaction is chemically converted into N2 O, and continuous‐flow isotope ratio mass spectrometry (CF‐IRMS) is used to determine the oxygen isotopic compositions. Results: The reciprocal of the NO3 − quantities on the nitrite‐coated filters in each sample showed a strong linear relationship with Δ 17 O of NO3 − . Using the linear relation, we corrected the changes in Δ 17 O of NO3 − on the filters. We verified the accuracy of the new method through the measurement of artificial O3 with known Δ 17 O(O3 )term value that had been determined from the changes in Δ 17 O of O2 . The Δ 17 O(O3 )term of tropospheric O3 was in agreement with previous studies. Conclusions: We accurately determined the δ 18 O and Δ 17 O values of tropospheric O3 by blank correction using our new method. Measurements of Δ 17 O(O3 )term of the ambient troposphere showed 1.1 ± 0.7‰ diurnal variations between daytime (higher) and nighttime (lower) due likely to the formation of the temperature inversion layer at night.